Arctic Tourism: Realities & Possibilities - Pashkevich, Albina (Högskolan Dalarna, Kulturgeografi, 2014)
This paper addresses human capital in the Arctic in relation to tourism. More specifically, with an ever-increasing number oftourists recognizing the attractiveness of the Arctic, tour companies are increasingly recognizing the opportunities. The media(typically southern media) sells the image, either before or after the tourists arrive, and communities are often left to deal with therepercussions – whether those are social, economic, environmental, or the like. Many of the repercussions are negative; however,even when perceived as positive they can create tensions within small communities and showcase a variety of capacity issues.This paper focuses on the realities and possibilities of tourism in the Arctic. It offers an up-to-date descriptive overview of tourismnumbers and valuations. In addition, ‘realities’ also focuses on the current suite of challenges and ‘possibilities’ addresses criticalquestions that need to be asked as tourism grows. We are in an uncertain age and academic critique of the Arctic tourismphenomenon is growing as quickly as the numbers. This paper is almost fully circumpolar in outlook, written by individuals fromthose jurisdictions, and aims to intersect with other sectors active in the Arctic.